2016
DOI: 10.1063/1.4952616
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of nanosecond ultraviolet laser pulses with reactive dusty plasma

Abstract: Even though UV laser pulses that irradiate a gas discharge are small compared to the plasma volume (≲3%) and plasma-on time (≲6 × 10−6%), they are found to dramatically change the discharge characteristics on a global scale. The reactive argon–acetylene plasma allows the growth of nanoparticles with diameters up to 1 μm, which are formed inside the discharge volume due to spontaneous polymerization reactions. It is found that the laser pulses predominantly accelerate and enhance the coagulation phase and are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…If one replaces the light source, one should verify that the transmission measurements do not affect the particle formation. The time evolution of φ RF does not suggest that this is the case with the transmission setup used in this work but it has been reported that irradiating a similar discharge with pulses from a UV laser drastically affected the particle formation [146]. In that case the transmission measurements would be invasive, which would eliminate one of its biggest advantages.…”
Section: Detection Of Small Nanoparticlesmentioning
confidence: 84%
“…If one replaces the light source, one should verify that the transmission measurements do not affect the particle formation. The time evolution of φ RF does not suggest that this is the case with the transmission setup used in this work but it has been reported that irradiating a similar discharge with pulses from a UV laser drastically affected the particle formation [146]. In that case the transmission measurements would be invasive, which would eliminate one of its biggest advantages.…”
Section: Detection Of Small Nanoparticlesmentioning
confidence: 84%
“…It should be noted that this stable 'mode' is induced by continuous laser irradiation of the dusty plasma at 10 Hz. Without laser irradiation, cyclic dust void formation is observed and the discharge is far from stable [26]. A dust void is a macroscopic region free of large (coagulated) nanoparticles and is frequently encountered in dusty plasmas [27][28][29][30][31][32].…”
Section: Nanoparticle Propertiesmentioning
confidence: 99%
“…A dust void is a macroscopic region free of large (coagulated) nanoparticles and is frequently encountered in dusty plasmas [27][28][29][30][31][32]. In [26], it is shown that UV laser pulses are able to suppress the formation of a void, thereby stabilizing the dusty plasma. More specifically, the formation of a void is related to growing nanoparticles and expands due to increased drag forces [33].…”
Section: Nanoparticle Propertiesmentioning
confidence: 99%
“…For instance, by interaction of high power lasers with molecular or atomic clusters, during which dusty plasma is created, high-energy electrons can be produced by three processes, i.e., inner ionization, outer ionization, and Coulomb explosion [34][35][36]. In some experiments, lasers are used in order to study the dynamics of different phenomena in dusty plasmas which some recent experiments about investigation of different exotic phenomena can be found in [37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%